Pengaruh Corporate Social Responsibility, Ukuran Perusahaan Dan Kualitas Audit Terhadap Manajemen Laba Dengan Kepemilikan Keluarga Sebagai Pemoderasi (Studi Empiris Pada Perusahaan Non-Keuangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022) - Aulia Putri Wulandari; Zamratul Meini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to obtain empirical evidence of factors that can influence earnings management with Corporate Social Responsibility (CSR) reports, Firm Size, and Audit Quality. The novelty of this research is to test whether the concentration of family ownership can moderate the impact of CSR, Firm size, and audit quality. The data used in this research are from non-financial companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. Data processing was carried out using Eviews 12. The sample was determined based on a purposive sampling technique which resulted in 25 company samples. The results of this research prove that CSR has a negative effect on earnings management, company size has a negative effect on earnings management and audit quality has a positive effect on earnings management. Furthermore, family ownership can be used to moderate the influence of CSR and audit quality on earnings management, but cannot moderate the influence of company size on earnings management. Keywords: Corporate Social Responsibility, Firm Size, Audit Quality, Family Ownership and Earnings Management